Artificial Intelligence as Digital Prose in Redefining Originality in Legal Discourse - Rijal Ibnu Sani; Suartini Suartini; Ahmad Ahmad; Tri Cahya Indra Permana (Indonesian Journal of Law and Policy Studies, 2025)
This research originates from the phenomenon of moralistic stigma and academic conservatism that tend to perceive the integration of Artificial Intelligence (AI) as a degradation of originality in legal scholarship. Historically and empirically, however, the evolution of intellectual instruments from the pen to the computer has consistently transformed modes of expression without ever extinguishing the essence of human thought itself. This study aims to deconstruct the myth of â€œhandwritten originalityâ€ while legitimizing AI as a lawful co-creative instrument within the domain of telematics legal writing. Employing a conceptual approach and historical-technological comparison, the research finds that in the era of digital disruption, the essence of originality no longer resides in the mechanical construction of diction, but rather in the authority of logical curation, data validation, and argumentative direction elements that remain fundamentally controlled by the human legal subject as the holder of intellectual agency. The analysis concludes that AI should be understood as â€œDigital Prose,â€ evolutionarily comparable to the transformative impact of the typewriter and office software revolutions of previous decades. Systemic resistance to this technology is thus interpreted as a manifestation of technophobia that is increasingly incompatible with contemporary standards of performance, efficiency, and accuracy in modern legal discourse. The study recommends a redefinition of academic ethics that is more inclusive of humanâ€“machine collaboration in advancing global legal literacy